2010
DOI: 10.1007/s11099-010-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to salinity in Silver buffaloberry (Shepherdia argentea) introduced to Qinghai high-cold and saline area, China

Abstract: Since 2002, Silver buffaloberry (Shepherdia argentea) has been introduced from North America in order to improve the fragile ecological environment in western China. To elucidate the salt-resistance mechanism of S. argentea, we conducted a test with two-year-old seedlings subjected to 0, 200, 400, and 600 mM NaCl solutions for 30 d. The results showed that significant salt-induced suppression of plant fresh mass (FM) and stem height of S. argentea seedlings occurred only at the highest salinity level (600 mM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…P N was positively correlated with g S under all stress levels (Table 1. ), which could explain why the reduction in g S caused a simultaneous decrease in both P N and E. Such an inhibitory effect on photosynthesis has also been reported in another plant 32 . The reduction in P N under salt and alkali stress is generally considered to be stomatal restriction caused by partial closure of stomata and decreased cell viability 33–35 .…”
Section: Discussionsupporting
confidence: 67%
“…P N was positively correlated with g S under all stress levels (Table 1. ), which could explain why the reduction in g S caused a simultaneous decrease in both P N and E. Such an inhibitory effect on photosynthesis has also been reported in another plant 32 . The reduction in P N under salt and alkali stress is generally considered to be stomatal restriction caused by partial closure of stomata and decreased cell viability 33–35 .…”
Section: Discussionsupporting
confidence: 67%
“…The Elaeagnaceae family is mainly distributed in Southeast Asia, with approximately 80 species in three genera (Nazir et al ., 2020). There are many economically valuable plants in this family, such as species of H. rhamnoides , Elaeagnus latifolia Linn., and Shepherdia argentea , which play important roles in nutritional beverages, pharmaceutical manufacturing, and ecological regulation (Qin et al ., 2010). Genomic resources are essential to promote the molecular breeding of seabuckthorn and evolutionary research on the Elaeagnaceae family.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that salinity stress predisposes photosystem II (PSII) to photoinhibitory damage (Lu et al 2002;Maricle et al 2007;Hichem et al 2009;Qin et al 2010Qin et al , 2011Sui et al 2010). However, very little attention has been paid to the responses of PSII to salinity stress and high-temperature stress in combination (Henley et al 2002).…”
Section: Introductionmentioning
confidence: 99%